X-ray diffraction studies of clay minerals in selected soils of Capricorn District in Limpopo Province. - Seabi, F. T. (My University, 2008)
Soil clay minerals are secondary minerals formed by low temperature reactions in the soil through weathering. These minerals are highly reactive and greatly influence the chemical and physical properties of many soils. Limpopo Province has a great diversity of soils that differ over a wide range of landscapes and climatic regions. Their diversity offer interesting research opportunities in terms of their physical and mineralogical properties. Weathering of the parent materials and soils over the past decades has lead to the production of a wide variety of soil clay minerals. The main chemical reactions, such as hydrolysis, hydration, dehydration, oxidation, reduction, and carbonation, take place in the solum as well as in the parent material and are responsible for the formation of new mineral products in the soil. Although clay minerals have been researched in South Africa, representation in terms of site specific research and their implication to agricultural practices is still lagging behind. This study investigated the distribution patterns of soil clay minerals and their agricultural implications on selected soils within Limpopo Province. Samples were obtained from 3 soil types namely, Inceptic, Oxidic and Plinthic soil types in the study area. X-ray diffraction (XRD) analyses, X-ray fluorescence spectrometry (XRF) and scanning electron microscopy (SEM) techniques were used in determining the soil mineralogy, soil chemistry and soil genesis of the samples. The selected soils were found to be dominated by kaolinite, smectite and quartz in their clay fraction with respect to XRD. Quartz were dominant within a percentage range of 50% – 75%, followed by kaolinite within the percentage range of 23% - 49%; and lastly smectite within the percentage range of 0% - 22%. Feldspar and mica were also present in trace to minor quantities. XRF analyses revealed a general decrease in the amount of SiO2 in the clay fraction as compared to the whole soil and rock fractions. Al2O3 and Fe2O3 showed an increase in the clay fraction with other elements in negligible amounts. The SEM analyses revealed hexagonally shaped thin platelets which are typical of kaolinite. The weathering of feldspar and mica played a role in the quantities of kaolinite and smectite detected in the samples. The samples indicate that an alteration from primary to secondary minerals has taken place, but still lack satisfactory conditions for complete weathering. The booklet form of the kaolinite minerals in the area suggests their residual origin whereas the smooth booklet form suggests a sedimentary origin.
Thesis (M.Sc. (Soil Science)) -- University of Limpopo, 2008
Keywords: X-ray diffraction imaging; Kaolinite; Smectite; Feldspar; Mica; Kaolinite; Smectite; Clay minerals; X-ray diffraction imaging